Pendampingan Orang dengan Skizofrenia oleh Kader Kesehatan Jiwa di Wilayah Kerja Puskesmas Krian - Rahmawati, Ratna Dewi; Suryanto (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
People with Schizophrenia (ODS) are people with mental disorders whose rights need to be fulfilled to receive treatment in order to recover optimally. Communities and even ODS families often do not understand that schizophrenia can be treated and requires family and community support. ODS actually often gets a negative stigma from society. Community Health Empowerment for Early-Detecting and Reintegrating of Schizophrenia (CHEERS) is a community empowerment program that helps ODS recovery, one of which is through the role of mental health cadres. Mental health cadres are tasked with assisting ODS, conducting early detection of mental disorders and conducting outreach about Schizophrenia to caregivers and the community. Compliance with taking medication from ODS received guidance from cadres. ODS conditions are more stable and not easy to recover with assistance from cadres. Family and community support for ODS is better, thereby increasing ODS recovery to be more optimal. Early detection and outreach about schizophrenia increases public understanding so that the negative stigma against ODS is reduced and ODS who have not received treatment receive treatment at health facilities.